Hydroprocessing of bio-crude from continuous hydrothermal liquefaction of microalgae. (1st November 2015) - Biller, Patrick; Sharma, Brajendra K.; Kunwar, Bidhya; Ross, Andrew B.
Abstract : Graphical abstract: Highlights: Novel continuous HTL reactor for microalgae is presented. Residence times of 1–6 min resulted in up to 40% bio-crude yields. Lower residence time resulted in higher O in bio-crude. Hydroprocessing of bio-crude results in reduction of N and O. Further reduction of O using solvent extraction possible. Abstract: Hydrothermal liquefaction (HTL) has developed as one of the most promising technologies for biofuel production from wet biomass feedstocks in recent years. In the current study, a microalgae slurry was processed in a continuous flow hydrothermal processing unit capable of 2.5 l/h flow rates, temperatures of 350 °C and pressure of up to 206 bar. 40 wt.% bio-crude yields were obtained when processing Chlorella at residence times of 1.4 and 5.8 min . The higher heating value of the bio-crude was approximately 35 MJ/kg, however the nitrogen content of 6% and oxygen content of 11% render it unsuitable for direct combustion. In order to investigate the upgrading potential, the bio-crude was hydroprocessed using CoMo and NiMo catalysts at two temperatures (350 °C and 405 °C) in a stirred reactor. Both catalysts showed similar activity during hydroprocessing. Nitrogen content was typically reduced by 60% at 405 °C whereas oxygen content was reduced by 85%. Fractionation of the upgraded oils result in approximately 25% gasoline, 50% diesel and 25% heavy fuel oil fractions. Further analysis of oils by GC–MS, Sim-Dis and elemental analysis give insight into the fuel quality and nitrogen fractionation. The majority of oxygen is shown to be associated with high molecular weight material and can be reduced further following solvent extraction of the oils while the nitrogen content could only be reduced slightly.